Cytology of low‐grade cribriform cystadenocarcinoma in salivary glands: Cytological and immunohistochemical distinctions from other salivary gland neoplasms. Issue 3 (21st December 2015) - Ohta, Yoshiki; Hirota, Yuko; Kohno, Yohko; Kishimoto, Koji; Norose, Tomoko; Ohike, Nobuyuki; Takimoto, Masafumi; Shiokawa, Akira; Ota, Hidekazu
Abstract : Low‐grade cribriform cystadenocarcinoma of the parotid gland is rare malignancy that is classified as a variant of cystadenocarcinoma. In routine cytologic slides from fine‐needle aspiration of a parotid gland, we found several pseudopapillary clusters comprising mucus‐producing cells. They included a few tumor cells having three‐dimensional nuclear atypia and slight hyperchromatism, although most of the tumor cells showed bland nuclei. Our initial cytological diagnosis was: "Indeterminate. Uncertain whether cystadenocarcinoma or cystadenoma." The subsequent histological diagnosis was low‐grade cribriform cystadenocarcinoma. Immunohistochemical staining showed diffuse and strong reactivity for S‐100; tumor nests that were rimmed by p63 + cells, which suggests intraductal proliferation. Here, we report cytomorphological findings of this case, and discuss cytological and immunohistochemical distinctions between low‐grade cribriform cystadenocarcinoma and other salivary gland tumors, including a review of the literature. Diagn. Cytopathol. 2016;44:241–245. © 2015 Wiley Periodicals, Inc.